The Role of Literature in the Education of Fifth Grade Students in Elementary School from the Perspective of Textbooks in the Language Area from 2020 to 2022 - Uribe Hincapie, Richard Alonso; Ángel Sánchez, Verónica (UNIVERSIDAD ANTONIO NARIÑO, 2023)
Introduction: This article presents an analysis of the role that literature plays in the training processes of fifth-grade children, in order to understand its function in textbooks and the relationships that are woven with training at school. Methodology: This study had a qualitative approach based on documentary research criteria and assumed a hermeneutic scope. The research was developed from the inquiry in six textbooks in the language area used in educational institutions in the city of Medellín (Colombia) between the years 2020 and 2022. Results and Discussion: The diversity of positions and ways of using literature in textbooks generates ambiguous and even contradictory understandings in relation to its role in the formation of students. Likewise, dichotomies are referred to between the transcendence of literature and the specific role that it fulfills in terms of textbooks, to the extent that these are considered as unalterable guides to direct the teaching and learning processes. Conclusions: Literature is a key study object in textbooks, given its formative importance and the possibilities of these to promote comprehensive learning in students; However, their diversity and varied and contradictory positions prevent them from forming in an integral way in the academic, political and aesthetic aspects, which is why it is unavoidable to rethink them in relation to well-rounded education.